End-on cyanate or end-to-end thiocyanate bridged dinuclear copper(ii) complexes with a tridentate Schiff base blocking ligand: synthesis, structure and magnetic studies. (3rd January 2018) - Khan, Samim; Sproules, Stephen; Natrajan, Louise S.; Harms, Klaus; Chattopadhyay, Shouvik
Abstract : Two new dinuclear Schiff base copper(ii ) complexes have been synthesized and characterized. Copper(ii ) centres are ferromagnetically coupled in1 and antiferromagnetically coupled in2 . Abstract : Two dinuclear copper(ii ) complexes, [Cu2 (L)2 (μ1, 1 -NCO)2 ] (1 ) and [Cu2 (L)2 (μ1, 3 -NCS)2 ]·H2 O·DMF (2 ), have been synthesized using a tridentate N2 O donor Schiff base ligand (HL), [1((2-(ethylamino)ethylimino)methyl)naphthalen-2-ol], and characterized by elemental analysis, spectral study and X-ray crystallography. Both complexes are centrosymmetric dimers in which square pyramidal copper(ii ) centres are connected by pseudo-halides: end-on cyanate in1 and end-to-end (EE) thiocyanate in2 . Variable temperature (2–300 K) magnetic susceptibility measurements indicate the presence of ferromagnetic exchange coupling between copper(ii ) centres in complex1 ( J = 0.97 cm −1 ), and antiferromagnetic exchange coupling in2 ( J = −0.6 cm −1 ).